2018
DOI: 10.3892/ol.2018.9216
|View full text |Cite
|
Sign up to set email alerts
|

Novel ELISA for serodiagnosis of nasopharyngeal carcinoma based on a B cell epitope of Epstein‑Barr virus latent membrane protein 2

Abstract: Epstein-Barr virus (EBV) is widespread and is associated with nasopharyngeal carcinoma (NPC). Serological detection of EBV is commonly used for screening, diagnosis and epidemiological surveys of NPC. In the present study, a novel B cell multi-epitope peptide fusion protein (EBV-LMP2-3B), which is composed of three B cell linear epitopes (RIEDPPFNSLL, TLNLT and KSLSSTEFIPN) of EBV latent membrane protein 2 (LMP2), was expressed in a prokaryotic expression system and purified using Ni2+-nitrilotriacetate-Sephar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…EBV, known as human herpesvirus 4, can lead to many diseases, including infectious mononucleosis, lymphoma, nasopharyngeal carcinoma (NPC), etc. It is a virus commonly susceptible to almost all populations and can cause serious physical damage to patients [ 98 , 99 , 100 ]. As serological testing is available and important for diagnosing EBV infection, as well as usually being targeted by the viral capsid antigen, EBV nuclear antigen and early antigen, the introduction of epitopes will greatly facilitate the development of serological diagnosis.…”
Section: Applications In Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…EBV, known as human herpesvirus 4, can lead to many diseases, including infectious mononucleosis, lymphoma, nasopharyngeal carcinoma (NPC), etc. It is a virus commonly susceptible to almost all populations and can cause serious physical damage to patients [ 98 , 99 , 100 ]. As serological testing is available and important for diagnosing EBV infection, as well as usually being targeted by the viral capsid antigen, EBV nuclear antigen and early antigen, the introduction of epitopes will greatly facilitate the development of serological diagnosis.…”
Section: Applications In Diagnosismentioning
confidence: 99%
“…Studies have shown that EBV latent membrane protein 2 (LMP2) plays an important role in the pathogenesis of EBV-associated tumors. Therefore, many scientists have focused on the epitope of EBV LMP2, expecting to design a promising screening and diagnostic tool for NPC [ 98 , 102 , 103 ]. Among them, a novel B cell multi-epitope peptide fusion protein (EBV-LMP2-3B) has been constructed, which consists of three linear B cell epitopes of EBV LMP2.…”
Section: Applications In Diagnosismentioning
confidence: 99%
See 1 more Smart Citation